2023
DOI: 10.3389/fpsyg.2023.1265529
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from COVID-19?: examining the resilience of primary care teams

Ashley M. Hughes,
Kelley Arredondo,
Houston F. Lester
et al.

Abstract: IntroductionThe COVID-19 pandemic continues to place an unprecedented strain on the US healthcare system, and primary care is no exception. Primary care services have shifted toward a team-based approach for delivering care in the last decade. COVID-19 placed extraordinary stress on primary care teams at the forefront of the pandemic response efforts. The current work applies the science of effective teams to examine the impact of COVID-19—a crisis or adverse event—on primary care team resilience.MethodsLittle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Amidst a major crisis such as the COVID-19 pandemic, some research has identified interprofessional collaboration or teamwork as apotential protective factor among others, influencing the mental strain experienced by healthcare professionals. However, the relationships and individual impacts have not yet been investigated as a standalone research question concerning crisis management and mental well-being ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amidst a major crisis such as the COVID-19 pandemic, some research has identified interprofessional collaboration or teamwork as apotential protective factor among others, influencing the mental strain experienced by healthcare professionals. However, the relationships and individual impacts have not yet been investigated as a standalone research question concerning crisis management and mental well-being ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%